The Long-Term Effects of the Youth Crime Prevention Program "New Perspectives" on Delinquency and Recidivism - de Vries, Sanne L. A. (International journal of offender therapy and comparative criminology, 2018)
New Perspectives (NP) aims to prevent persistent criminal behavior. We examined the long-term effectiveness of NP and whether the effects were moderated by demographic and delinquency factors. At-risk youth aged 12 to 19 years were randomly assigned to the intervention group (NP, n = 47) or care as usual (CAU, n = 54). Official and self-report data were collected to assess recidivism. NP was not more effective in reducing delinquency levels and recidivism than CAU. Also, no moderator effects were found. The overall null effects are discussed, including further research and policy implications.